GOODS AND SERVICES TAX: A STUDY ON ROAD MAP FOR 2017 - Nidhi (International Journal of Research -GRANTHAALAYAH, 2016)
The paper covers the scope of GST and the history of the taxation system in India. The word tax is derived from the Latin word ‘taxare’ meaning, to estimate. “A tax is not a voluntary payment or donation, but an enforced contribution, exacted pursuant to legislative authority" and is any contribution imposed by government whether under the name of toll, tribute, impost, duty, custom, excise, subsidy, aid, supply, or other name.” Taxes in India are levied by the Central Government and the State Governments. Some minor taxes are also levied by the local authorities such as Municipality or Local Council. The paper consists of the demerits of existing taxation system, challenges and opportunities of the GST and the latest amendments with the road map for 2017. With the help of this paper we get the overview of the current amendments and the future efforts to be made in the implementation of GST.